Medveten om vad? En rättsdogmatisk undersökning av medvetenhetskravets innebörd för straffrättsligt ansvar - Slagbrand,Miranda (2025)
The consciousness requirement is a prerequisite for criminal liability and means that a person must have been sufficiently conscious in order to be aware of his or her actions. The consciousness requirement is not regulated in law, it has developed through practice and doctrine. The purpose of the essay is to clarify the consciousness requirement in Swedish criminal law and to examine its potential impact on legal certainty for the defendant. The questions that this essay is based on are the following: What is the current law for the requirement of awareness? Can the awareness requirement, as it appears in current law, lead to problems regarding legal certainty? The legal dogmatic method has been used to answer the questions and the material has been doctrine and two court cases. The analysis concludes that there are major differences in the perception of the consciousness requirement. According to doctrine consciousness can mean bodily control and not being in an excessively dazed state. But consciousness can also refer to awareness regarding circumstances and consequences, i.e. awareness of the act itself. In these cases, it is about consciousness in the sense of having knowledge of something. In the legal cases, consciousness has been highlighted in relation to the requisites of the act or as a fundamental state of mind. The definition of consciousness is, as can be seen, unclear, which may mean that the principle of conformity and the principle of foreseeability are not maintained, which poses problems for the legal certainty of liability assessment.
Keywords: straffrätt